Radiosynthesis and preliminary evaluation of 11C-labeled 4-cyclopropyl-7-(3-methoxyphenoxy)-3, 4-dihydro-2H-benzo[e] [1, 2, 4] thiadiazine 1, 1-dioxide for PET imaging AMPA receptors. Issue 12 (19th March 2020) - Chen, Jiahui; Gan, Jiefeng; Sun, Jiyun; Chen, Zhen; Fu, Hualong; Rong, Jian; Deng, Xiaoyun; Shang, Jingjie; Gong, Jian; Shao, Tuo; Collier, Lee; Wang, Lu; et al.
Graphical abstract: Highlights: New radiosynthetic route to a 11 C-labeled AMPA ligand. High radiochemical yield and high molar activity. Pharmacokinetic profile established for further optimization. Abstract: The α -amino-3-hydroxyl-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) belong to the family of ionotropic transmembrane receptors for glutamate (iGluRs) that are implicated in the pathology of neurological disorders and neurodegenerative diseases. Inspired by a recently developed positive allosteric modulator of AMPARs, 4-cyclopropyl-7-(3-methoxyphenoxy)-3, 4-dihydro-2 H -benzo[ e ][1, 2, 4]thiadiazine 1, 1-dioxide (16 ; EC50  = 2.0 nM), we designed a new synthetic route for N -protected phenolic precursor 13 and efficiently radiolabeled a PET ligand [ 11 C]AMPA-1905 ([ 11 C]16 ) using a modified one-pot two-step strategy in high radiochemical yield and high molar activity. Preliminary in vivo evaluation was carried out to investigate the suitability of [ 11 C]16 as a potential PET probe for AMPAR imaging.